Patai's Chemistry of Functional Groups 2009
DOI: 10.1002/9780470682531.pat0189
|View full text |Cite
|
Sign up to set email alerts
|

Acyl Silanes

Abstract: Introduction Structure and Spectroscopy of Acyl Silanes Synthesis of Acyl Silanes Reactions of Acyl Silanes Conclusion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 243 publications
(213 reference statements)
1
3
0
Order By: Relevance
“…Compared to compound 3 , an example of an aryl-substituted acylgermane, a significantly hypsochromic shift occurs (Figure ). This is not surprising because it is well-known that aliphatic substituents at the carbonyl moieties undergo the same hypsochromic shift. , Moreover, the absorption spectrum of 1 and 2 exhibits considerable fine structure consisting of four main bands which is not unusual and parallels the behavior of structurally related acyl group 14 compounds . Nevertheless, to synthesize high performance visible light photoinitiators, these blue-shift significantly, lowering the activity of these derivatives, when visible light is used.…”
supporting
confidence: 92%
“…Compared to compound 3 , an example of an aryl-substituted acylgermane, a significantly hypsochromic shift occurs (Figure ). This is not surprising because it is well-known that aliphatic substituents at the carbonyl moieties undergo the same hypsochromic shift. , Moreover, the absorption spectrum of 1 and 2 exhibits considerable fine structure consisting of four main bands which is not unusual and parallels the behavior of structurally related acyl group 14 compounds . Nevertheless, to synthesize high performance visible light photoinitiators, these blue-shift significantly, lowering the activity of these derivatives, when visible light is used.…”
supporting
confidence: 92%
“…The sum of the bond angles around the carbonyl C atom in 16a , b is close to 360° and reflects the trigonal-planar geometry within the SiRCO moiety. Unexceptional carbonyl CO bond lengths of 1.21 and 1.23 Å were measured, while the silicon carbonyl group bond distances at 1.97 and 1.96 Å are considerably elongated relative to the length of an average Si–C­(sp 3 ) bond, as observed earlier for other acyl silanes . In order to minimize steric congestion, the bulky t -Bu or Ad groups are oriented toward the outside of the molecules, which brings the carbonyl oxygen atoms in 16a , b in rather close contact to the endocyclic Si–Si bond system, with nonbonding distances to the plane defined by Si(1), Si(2), and Si(6) of only 2.66 and 2.65 Å, respectively.…”
Section: Resultsmentioning
confidence: 58%
“…Unexceptional carbonyl C=O bond lengths of 1.21 and 1.23 Å were measured, 23 while the silicon carbonyl group bond distances at 1.97 and 1.96 Å are considerably elongated relative to the length of an average Si–C(sp 3 ) bond, 24 as observed earlier for other acyl silanes. 25 In order to minimize steric congestion, the bulky t -Bu or Ad groups are oriented toward the outside of the molecules, which brings the carbonyl oxygen atoms in 16a , b in rather close contact to the endocyclic Si–Si bond system, with nonbonding distances to the plane defined by Si(1), Si(2), and Si(6) of only 2.66 and 2.65 Å, respectively. This structural feature will gain importance because it can be used to rationalize the unprecedented course of the photolysis experiments described in the next section of this paper.…”
Section: Resultsmentioning
confidence: 99%
“…Silicon carbonyl group bond lengths at 1.92–1.94 Å are considerably elongated, the average Si–C­(sp 3 ) bond length was calculated from 19 169 individual XRD experimental values to be 1.860 Å . Significantly elongated Si–C bond distances in acyl silanes have been observed earlier, and it has been suggested that this lengthening of the silicon carbonyl group bond can be ascribed not only to contributions of canonical forms with single C–O bonds (Scheme , structure A), but also to a resonance structure without a formal bond between the metalloid atom and the carbonyl carbon (Scheme , structure B) . According to a more recent study, finally, the situation is best described by structure C with a dative bond between a negatively charged carbon and a positively charged silicon atom …”
Section: Resultsmentioning
confidence: 84%